The Legal Impact and Relevance of Using Plea Bargains to Resolve Tax Disputes in Nigeria - Aidonojie, Paul Atagamen (Faculty of Law, Universitas Brawijaya, 2022)
Governments use taxes to generate the revenue needed to provide basic facilities for society. However, taxpayers may evade tax liabilities or default, compelling tax authorities to resort to quasi-criminal litigation to recover taxes. Evidently, the process involved in prosecuting tax defaulters or recovering tax liabilities as provided for in the Personal Income Tax Act of Nigeria and as observed in a plethora of cases is often strenuous, cumbersome, and bureaucratic. Furthermore, the process is slow, and is unfriendly to taxpayers; hence, plea bargains are needed in prosecuting tax cases involving tax liabilities. In this study, online questionnaires were sent to 321 respondents (randomly selected) residing within the federal republic of Nigeria to ascertain the utility and favorability of using plea bargains to resolve liabilities. Descriptive and analytical statistics were used to analyze the collected data. The study found that plea bargains are viable prosecutorial tools for resolving tax offenses or recovering tax liabilities. Therefore, this study recommends using plea bargains owing to its speed in resolving tax offenses or recovering tax liabilities and its less bureaucratic and more amicable nature compared to quasi-criminal litigation.